The 3rd European Race Walking Conference (New Studies in Athletics, 2018)
Zusammenfassender Bericht der 3. Internationalen Konferenz zum Sportgehen an der Leeds Beckett University, Emgland (GBR) vom 11.-13. November 2016. Mit kurzen Zusammenfassungen folgender Beiträge: - Eleonora Giorgi - Development and increase of her perfomance (G. Perricelli, ITA), - Racewalk West - What we've learned (G. Dragomir, CAN), - Pacing in race walking (B. Hanley, IRL), - Biomechanics Workshop (B. Hanley/IRL, C. Tucker, IRL, H. Gravenstock, GBR), - Technical Workshop (G. Dragomir/CAN, G. perricelli, ITA), - Nutrition support to a world U23 Champion) (C. Sloss), - In pursuit of clean sport (S. backhouse, GBR), - Lessons from serial winning coaches (S. lara-Bercial, ESP), - Tom Bosworth: Athlete, coach & support team development 2009-2016 (A. Drake/GBR, B. Hanley/GBR, L. Susson/GBR, A. Manley/GBR). Weitere Zusammenfassungen gibt es zu den Themen Coaching, Physiologie, Biomechanik, Ernährung und Psychologie.